The Demand for Literature in France, 1769–1789, and the Launching of a Digital Archive - Darnton, Robert (Mémoires du livre / Studies in Book Culture, 2016)
What did the French read on the eve of the Revolution? Daniel Mornet asked this question in a famous article of 1910. Since then, historians have moved on to other ways of understanding the origins of 1789, but Mornet’s question has been left hanging, despite its relevance to recent work in fields such as the history of books and cultural history in general. This essay is intended to provide an answer to Mornet’s question while at the same time introducing an open-access website full of information about the demand for literature and the way the book trade actually operated under the Ancien Régime.